2011
DOI: 10.1021/ol103081y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amides via Palladium-Catalyzed Amidation of Aryl Halides

Abstract: A new and efficient method for the synthesis of amides via palladium-catalyzed C-C coupling of aryl halides with isocyanides is reported, by which a series of amides were formed from readily available starting materials under mild conditions. This transformation could extend its use to the synthesis of natural products and significant pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(66 citation statements)
references
References 51 publications
2
62
0
2
Order By: Relevance
“…Apart from a very recent computational report, to the best of our knowledge, no study has appeared in the literature concerning this kind of transformation. Among the comparatively few literature examples of intermolecular imidoylative couplings with simple nucleophiles, the study case we chose for our work is the elegantly simple reaction reported in 2011 by Jiang and co‐workers for the Pd‐catalyzed synthesis of secondary amides from an aryl halide, an isocyanide, and water in the presence of CsF as a base (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…Apart from a very recent computational report, to the best of our knowledge, no study has appeared in the literature concerning this kind of transformation. Among the comparatively few literature examples of intermolecular imidoylative couplings with simple nucleophiles, the study case we chose for our work is the elegantly simple reaction reported in 2011 by Jiang and co‐workers for the Pd‐catalyzed synthesis of secondary amides from an aryl halide, an isocyanide, and water in the presence of CsF as a base (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Johnston and co-workers showed a non-conventional amide synthesis via iodonium-promoted nitroalkane-amine coupling 11 and our group reported an efficient method for the synthesis of amides via palladium-catalyzed CeC coupling of aryl halides with isocyanides. 12 On the other hand, terminal alkynes and haloalkynes are readily accessible materials and remarkable progress has been made through transition-metalcatalyzed reactions in the past decades. Recently, terminal alkynes were transformed to the corresponding amides 13 and haloalkynes were used to synthesize ynamides efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…A domino process involving oxidative addition of N ‐(2‐iodophenyl)methacrylamide derivative 6 to Pd 0 , intramolecular alkene insertion, and imidoylative cyclization of the resulting C sp 3Pd II intermediate with α‐isocyanoacetamide 1 a , was realized to install an oxindole moiety on the oxazole with a methylene tether (Equation 1, 7 a and 7 b ). Isocyanide insertion into a C sp 3Pd II intermediate is rare 3b…”
Section: Resultsmentioning
confidence: 99%